Clinical Perspective on Passive Audio Vocal Measurement in the Evaluation of Selective Mutism - Xu, Helen Y.; Stroud, Jacob; Jozanovic, Renee K.; Clucas, Jon; Son, Jake Jungwoo; Koo, Bonhwang; Schwarz, Juliet; Klein, Arno; Busman, Rachel; Milham, Michael P. (Frontiers in Psychiatry, 2018)
Selective Mutism (SM) is an anxiety disorder often diagnosed in early childhood and characterized by persistent failure to speak in certain social situations but not others. Diagnosing SM and monitoring treatment response can be quite complex, due in part to changing definitions of and scarcity of research about the disorder. Subjective self-reports and parent/teacher interviews can complicate SM diagnosis and therapy, given that similar speech problems of etiologically heterogeneous origin can be attributed to SM. The present perspective discusses the potential for passive audio capture to help overcome psychiatry's current lack of objective and quantifiable assessments in the context of SM. We present supportive evidence from two pilot studies indicating the feasibility of using a digital wearable device to quantify child vocalization features affected by SM. We also highlight comparative analyses of passive audio capture and its potential to enhance diagnostic characterizations for SM, as well as possible limitations of such technologies.